Epidemiology of lobomycosis-like disease in bottlenose dolphins Tursiops spp. from South America and southern Africa - Van Bressem, Marie-Françoise; Simões-Lopes, Paulo C; Félix, Fernando; Kiszka, Jeremy J; Daura-Jorge, Fabio G; Avila, Isabel C; Secchi, Eduardo R; Flach, Leonardo; Fruet, Pedro F; du Toit, Kate; Ott, Paulo H; Elwen, Simon; et al. (Diseases of aquatic organisms, 2015)
We report on the epidemiology of lobomycosis-like disease (LLD), a cutaneous disorder evoking lobomycosis, in 658 common bottlenose dolphins Tursiops truncatus from South America and 94 Indo-Pacific bottlenose dolphins T. aduncus from southern Africa. Photographs and stranding records of 387 inshore residents, 60 inshore non-residents and 305 specimens of undetermined origin (inshore and offshore) were examined for the presence of LLD lesions from 2004 to 2015. Seventeen residents, 3 non-residents and 1 inshore dolphin of unknown residence status were positive. LLD lesions appeared as single or multiple, light grey to whitish nodules and plaques that may ulcerate and increase in size over time. Among resident dolphins, prevalence varied significantly among 4 communities, being low in Posorja (2.35%, n = 85), Ecuador, and high in Salinas, Ecuador (16.7%, n = 18), and Laguna, Brazil (14.3%, n = 42). LLD prevalence increased in 36 T. truncatus from Laguna from 5.6% in 2007-2009 to 13.9% in 2013-2014, albeit not significantly. The disease has persisted for years in dolphins from Mayotte, Laguna, Salinas, the Sanquianga National Park and Bahía Málaga (Colombia) but vanished from the Tramandaí Estuary and the Mampituba River (Brazil). The geographical range of LLD has expanded in Brazil, South Africa and Ecuador, in areas that have been regularly surveyed for 10 to 35 yr. Two of the 21 LLD-affected dolphins were found dead with extensive lesions in southern Brazil, and 2 others disappeared, and presumably died, in Ecuador. These observations stress the need for targeted epidemiological, histological and molecular studies of LLD in dolphins, especially in the Southern Hemisphere.